10. PILGUB JAWA TENGAH 2008 BERPACU DENGAN UNDANG-UNDANG - Pradhanawati, Ari (FORUM, 2008)
Governor and Vice Governor Election 2008 is organized based on the Law Number 32, 2004, on Local Government which was the revised twice with Law N 22, 2007, on General Election, and Law Number 12, 2008 on the Second Revision of Law Number 32, 2004. These three laws are made use as the right base of Central Java Governor Election 2008 in the condition of racing with the law. However, these three laws are less implementative.